NaFeSi2O6 nanocrystals as a catalyst for heterogeneous photo-Fenton degradation of organic wastewater. Issue 34 (18th August 2022) - Zhang, Lulu; Zhang, Hongwen; He, Jingxuan; Li, Na; Zhang, Yipin; Sun, Yaxin; Deng, Xinyue; Zhao, Mengjun; Ran, Weiguang; Yuan, Jie; Liu, Ping; Yan, Tingjiang
Abstract : In this work, a novel, earth-abundant, and environmentally benign NaFeSi2 O6 catalyst is synthesized by a one-step solvothermal method without the introduction of any surfactants. Abstract : In this work, a novel, earth-abundant, and environmentally benign NaFeSi2 O6 catalyst is synthesized by a one-step solvothermal method without the introduction of any surfactants. NaFeSi2 O6 is for the first time applied to the heterogeneous photo-Fenton reaction for the degradation of RhB under visible-light irradiation with long-term stability and a wide working pH range. ˙OH plays the most important role in the photo-Fenton process. Besides, ˙O2 − and h + are also generated and involved in this reaction simultaneously. Combining the experimental results and theoretical calculations, it can be confirmed that NaFeSi2 O6 can be regarded as a promising catalyst to improve the efficiency of the heterogeneous photo-Fenton reaction.